Standardization of electrochemical technique for the determination of titanium in samples of pharmaceuticals and industrial waste - Jeaneth Marisol Medina Pérez (2019)
There are no methods in our town to determine Ti (IV) in samples. In this work we used an electrochemical sensitive method to determine Ti (IV). It is based on formation of a complex with cupferron in acid solution. The analysis was made in a voltamperomnietric station equipped with a drop mercury electrode (HMDE) a reference electrode Ag/AgCl and an auxiliary platinum electrode. A buffer of ammonium acetate pH 5 and a solution of cupferron 1x10^-3 mol.dm3. The peak resulting from complex formation is proportional to concentration of Ti (IV) . the detection limit was 7 mg.L^-1 obtained under optimal experimental conditions . This method showed to be linear, exact and reproducible and was applied for determination of Ti (IV) in environmental samples and pharmaceutical products giving satisfactory results